2021
DOI: 10.3390/ma14123437
|View full text |Cite
|
Sign up to set email alerts
|

Fast Solution Synthesis of NiO-Gd0.1Ce0.9O1.95 Nanocomposite via Different Approach: Influence of Processing Parameters and Characterizations

Abstract: The synthesis of the nickel oxide-gadolinium doped ceria (NiO-GDC with 65:35 wt.%) nanocomposite powders with a stoichiometry of Gd0.1Ce0.9O1.95 was performed via fast solution combustion technique; using three different mixing methods: (i) CM (metal cations in an aqueous solution), (ii) HM (hand mortar), and (iii) BM (ball milling). The nanocomposite powders were calcined at 700 °C for 2 h and characterized by Transmission Electron Microscopy (TEM), X-ray fluorescence (XRF), and X-ray Diffraction XRD. The TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The comparison between theoretical and experimental values of the prepared samples analyzed by EDS exhibited a reasonable stoichiometric control in the synthesis process of the materials (Supplementary Material Figure S2). The effect of calcination in the optimization of the desired stoichiometry was corroborated, because the increase in the calcination temperature led to the differences between the theoretical and experimental values, which were considerably reduced [40,41]. Table 3 shows the apparent density and porosity compared with the grain size and microhardness of the samples.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…The comparison between theoretical and experimental values of the prepared samples analyzed by EDS exhibited a reasonable stoichiometric control in the synthesis process of the materials (Supplementary Material Figure S2). The effect of calcination in the optimization of the desired stoichiometry was corroborated, because the increase in the calcination temperature led to the differences between the theoretical and experimental values, which were considerably reduced [40,41]. Table 3 shows the apparent density and porosity compared with the grain size and microhardness of the samples.…”
Section: Resultsmentioning
confidence: 78%
“…: 98-009-9555). Previous experience has shown the existence of polymorphs with identical nominal compositions during the formation of the LSM phase with this synthesis method [40,41]. In order to study the structural properties of the samples in detail, Rietveld refinements were performed using TOPAS software (Bruker AXS) with the double Voigt function [42].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, as GDC possesses ionic conductivity, more ionic contribution to the electrical properties of nanowires grown at 1450 °C can be expected. 22 For further investigation of structural and compositional analysis nano-Raman spectroscopy has been performed.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible reason can be the variation in the concentration of NiO and GDC contents in the nanowires. 22 It has been observed that high NiO concentration in the NiO-GDC composite improves the conductivity due to the domination of electronic conduction while high GDC concentration enhances the ionic charge transport, which results in low electrical conductivity of the composite. 22 As we have already seen for XRD investigations, the nanowires grown at 1450 1C exhibit a higher concentration of GDC as compared to nanowires deposited at 1400 1C.…”
Section: Electrical Properties Of Nio-gdc Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation